UJI RESISTENSI BAKTERI TERHADAP HgCl, YANG DIISOLASIDARI TANAH PENAMBANGAN EMAS DIPONGKOR, JAWA BARAT - Hartati Imamuddin (BERITA BIOLOGI, 2011)
Pollution of heavy metals mercury (Hg) is a serious problem especially in gold mining areas. This study aims to isolate the bacteria in the gold mining of Pongkor (West Java) and testing the bacterial resistance to mercury (Hg). The results showed that of the 5isolates tested, qualitatively only 2 isolates (P3 and P5) that resistant to HgCI2, each at a concentration of 30 and 40 ppm.Furthermore, up to 70 ppm concentration of HgCl2, P5 bacteria can still grow well even require a longer time lag phase in period.